2019
DOI: 10.3855/jidc.11267
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status evaluation and nutrient intake in adult patients with pulmonary tuberculosis and their contacts

Abstract: Introduction: Malnutrition is a common status in patients with tuberculosis (TB). Because TB is disseminated through the sputum of infected persons, individuals who maintain relations with a TB patient are at high risk of infection; this risk is greater when contacts present an inadequate nutritional status. The aim of this work was to analyse and compare the nutritional status and macro and micronutrient intake of TB patients and their household contacts. Methodology: A cross-sectional study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…In this study, tuberculosis patients had a lower BMI than healthy controls, as previous studies 34 . We also observed a high incidence of low‐weight malnutrition in tuberculosis patients compared with the control group, which was mainly caused by anorexia, malabsorption, and inflammation‐driven catabolism, 35 increasing the risk of anorexia and underweight 36 .…”
Section: Discussionsupporting
confidence: 82%
“…In this study, tuberculosis patients had a lower BMI than healthy controls, as previous studies 34 . We also observed a high incidence of low‐weight malnutrition in tuberculosis patients compared with the control group, which was mainly caused by anorexia, malabsorption, and inflammation‐driven catabolism, 35 increasing the risk of anorexia and underweight 36 .…”
Section: Discussionsupporting
confidence: 82%
“…Both the groups were deficient in energy, fiber, carbohydrate, and micronutrient (vitamins and minerals) intake, with a higher lipid and protein intake. Consistent with other results, the active patients presented lower BMI than HCs (Campos-Gongora et al, 2019 ). The groups also showed deficiencies in minerals such as copper, iron, magnesium, calcium, and zinc (Chan and Chan, 1994 ; Edem et al, 2015 ; Campos-Gongora et al, 2019 ).…”
Section: Alteration Of Micronutrient Profile During Tbsupporting
confidence: 91%
“…Consistent with other results, the active patients presented lower BMI than HCs (Campos-Gongora et al, 2019 ). The groups also showed deficiencies in minerals such as copper, iron, magnesium, calcium, and zinc (Chan and Chan, 1994 ; Edem et al, 2015 ; Campos-Gongora et al, 2019 ). Another study estimated that the proportion of vitamin A deficiency in TB patients and controls was 56.4% and 39.0%, respectively, and all patients and 92.5% of controls were recognized with zinc deficiency (Ghulam et al, 2009 ; Keflie et al, 2018 ).…”
Section: Alteration Of Micronutrient Profile During Tbsupporting
confidence: 91%
“…27 In anthropometric assessments using BMI based on a study by Gongora, et al (2019), most of the study population showed poor nutrition. 28 Only around 30% of TB patients and contacts showed normal BMI. 28 Kadri, et al (2022) in Padang showed that patients with DS and DR TB had malnutrition condition, whereas nutritional status had odds ratio (OR) of 10.92 as one of the risk factors for DR TB.…”
Section: Discussionmentioning
confidence: 99%
“…28 Only around 30% of TB patients and contacts showed normal BMI. 28 Kadri, et al (2022) in Padang showed that patients with DS and DR TB had malnutrition condition, whereas nutritional status had odds ratio (OR) of 10.92 as one of the risk factors for DR TB. 29 In addition, Soeroto, et al (2020) also found that patients with DR TB and normal BMI had 1.21 times higher chance of successful treatment compared to patients with underweight BMI.…”
Section: Discussionmentioning
confidence: 99%